Variasi Konsentrasi Glukosa pada Media Tumbuh dan Lama Fermentasi Dalam Memproduksi Etanol oleh Isolat BM1-CP14 - Ajizah, Nurul Lita; Wijaya, I M. Mahaputra; Antara, Nyoman Semadi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2021)
This study was aimed determine the effect of glucose concentration on ethanol producing BM1-CP14 isolate media and to determine to optimum fermentation time to producing ethanol and to determine the growth phase curve of BM1-CP14 isolates. This study uses 4 glucose concentration (8, 12, 16 and 20%) and 3 fermentation time (14, 17 and 20 days). The experimental-explorative research process was carried out in several stages, namely rejuvenation of BM1-CP14 cultures, culture grow, cell isolates adjustment, glucose level on fermentation media measurement, fermentation, and distillation. The glucose concentration which are at the range of 10?18% have an optimum effect in producing ethanol The highest total ethanol was obtained from the glucose concentration of 16% with a fermentation time of 10 days having a difference in total dissolved solids of 8.30 (?% brix) resulting in the highest total ethanol of 38.75 mL. The glucose concentration of 8% resulted in a less than optimal total ethanol, which was 18.00 mL with a difference in total solids of 4.20 (?% brix), while the glucose concentration of 20% has a difference in total dissolved solids of 6.20 (?% brix) and produced a total ethanol of 26.50 mL. The Fermentation time of 14, 17, and 20 days was effected in producing ethanol, namely if the fermentation was longer, the total ethanol produces would be lower. The fermentation time of 14 days resulted in a total ethanol of 37.50 mL with a difference in total dissolved solids of 5.05 (?% brix). In longer fermentation of 17 and 20 days, the total ethanol produced was decreased, produced smaller total ethanol. The growth curve of BM1-CP14 isolates showed the growth isolates of BM1-CP14 with a growth time of 54 hours, starts from the exponential phase for 12 hours, the stationary phase for 1 8 hours and ends in the death phase. Keywords: B acteria, BM1-CP14 isolate , ethanol, fermentation time , glucose concentration